Student perceptions of place and belonging in online courses - Bryan Orthel; Dana Vaux; Michael Langlais (Journal of the Scholarship of Teaching and Learning)
Sense of place in learning environments supports students’ identity, belonging, and success. Online learning environments present unique conditions as students engage with others from distinct physical locations through shared virtual interfaces. Differences of location and technology may alter how students’ sense of place and community emerge in online learning courses. This article draws from literature on place and community before synthesizing findings from three sense of community scales for student perceptions of recent online courses. Results contradict and support previous research suggesting virtual platforms enhance identity and community by emphasizing human relationships. Recommendations for continued scholarship and teaching activities are discussed.